Productive and Physiological Responses of Heat-Stressed Dominant Black Hens to Artificial Ventilation and Modified Layers Mash in Nigeria - Fasanmi , O.G.; Okuneye, O.J.; Ajibola, E.S.; Oladele-Bukola, M.O.; Olona, J.F.; Ajayi, J.O.; Balogun, F.A. (International Journal of Poultry Science, 2015)
One thousand 53 weeks old heat stressed dominant black hens at 82% egg production were allotted into four treatment groups and used to determine the effects of ventilation and modified Layer’s mash (MLM) on productive and physiological parameters. Treatment 1 (T1) are birds housed with fan and fed layers mash. Treatment 2 (T2) are birds fed MLM with fans, treatment 3 (T3) were fed layers mash but no fans. Treatment 4 (T4) fed MLM but no fans. Data were subjected to percentages and two way ANOVA. T1 had the highest mean feed intake (114.56±0.035 gm) and T4 had the lowest consumption (107.87±0.086 gm). The highest mean weekly mortality (11.10±0.98) was recorded in T3 and the lowest 6.31±0.21 in T2. T2 had the highest mean % egg production (78.18±2.80) and the lowest percentage (68.37±3.10) in T3. The result of this study also revealed that both relative humidity (RH) and temperature correlated negatively and significantly with feed consumption across the treatments. The PCV of T1 (37.20±0.70) is equal to T2 (37.40±0.10), but significantly greater (p>0.05) than T3 (34.45±0.05) and T4 (34.20±0.50), the WBC followed same trend, while other haematological parameters show no significant differences. T2 has the most significant increase in serum globulin and Uric acid, followed by T1, all other parameters are not significantly different. The electrolytes (K+, Na+, Ca2+, Cl- and HCO3-) also followed the same trend. T2 has the best performance, therefore to alleviate the effects of heat stress, dietary modifications and good ventilation is recommended.